Role of anharmonicity in phonon-mediated superconductivity of quasi- van der Waals layered XP2 (X = As, Sb, Bi) structures: Insight from first-principles calculations - Tsuppayakorn-aek, Prutthipong; Pluengphon, Prayoonsak; Sukmas, Wiwittawin; Sakulkalavek, Aparporn; Inceesungvorn, Burapat; Luo, Wei; Bovornratanaraks, Thiti (My University, 2023)
It is of utmost importance to prioritize the undertaking of investigating superconductivity, as it represents one of the most intriguing and significant phenomena in the field of condensed matter physics. Our research endeavors to shed light on the metallic state of van der Waals layered XP2 (X = As, Sb, Bi) structures, which is crucial in predicting their superconducting properties. Employing a first-principle evolutionary algorithm, we predicted the structures of phosphides, including AsP2, SbP2, and BiP2, and determined their energetically stable configurations under atmospheric pressure. To investigate the potential for superconductivity in these structures, we conducted a thorough examination of relevant electronic properties. One of the crucial factors we addressed was the role of anharmonic phonon properties in determining the superconducting state in van der Waals layered structures. Our findings suggest that the introduction of anharmonicity can significantly suppress the superconducting abilities of such structures. Hence, the anharmonicity present in AsP2, SbP2, and BiP2 could be held accountable for the lower observed superconducting critical temperature in these van der Waals layered structures.
Keywords: Anharmonicity; First-principles calculations; Phonon; Superconductivity